Legal Implications of the Installation of Road Portals by the Community in Sungai Toman Village - Nudi Haryadi; Moh. Muhibbin; Diyan Isnaeni (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
Roads are key supporting facilities for land mobility, both for people and for land transportation vehicles transporting people and goods. Roads, as vital infrastructure, play a central role in supporting modern life. However, the function and sustainability of roads are often disrupted by various violations that harm the public interest. One form of violation of road utilization and management is the unauthorized installation of road portals.This research is a juridical-empirical legal study using a sociological juridical approach and a statutory regulatory approach (Stuttute Approach). The objectives of this research are to analyze and describe: (1) the government's role in regulating and supervising road portal installation, (2) the impact of road portal installation on public mobility, and (3) the legal implications of violations of road management and utilization. The data used are primary data from direct sources and secondary data from legal materials in the form of laws and regulations, scientific journals, and relevant documents. Data collection was conducted using interviews and literature review techniques. The research findings indicate that the installation of road portals in Sungai Toman Village constitutes a violation of the law regarding the implementation and utilization of road functions. In general, the government has the authority to regulate and supervise the installation of portals, the provisions of which are realized in Regional Regulation Number 29 of 2001 concerning Tonnage and Portals and Regional Regulation Number 9 of 2017 concerning the Implementation of Public Order. The installation of these portals has an impact on various aspects of community life, including impacts on public mobility, economic and commercial mobility, as well as impacts on social dynamics and horizontal conflict